Penerapan Metode Pembalajaran Berbasis Kolaboratif dalam Meningkatkan Keaktifan Belajar Siswa (Studi Kasus Siswa SMP Negeri 1 Warungkondang) - Suharyanto H. Soro; Maman Suherman; Abuy Abuy; Enyi Masrukoyah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Student activity in learning is one of the keys to teacher success in implementing teaching models. Teachers have several teaching models to apply to their students, and all of these models have advantages and disadvantages. Students in participating in learning both in class and in the field are not all active so that much of the material presented by the teacher is not understood. This can be seen from the low participation in discussions, minimal courage to ask questions, and lack of motivation to complete tasks together. This study aims to exploit collaborative-based learning models in increasing student activity in participating in all learning activities carried out by teachers both in class and in the field. This study uses a qualitative method with a case study approach. Sample selection is done by purposive sampling. Data collection methods use observation, interviews, and documentation studies. While the samples in the study were the principal, teachers, students. The results of the study show that (1) Collaborative-based learning models can increase student activity; (2) Students become more enthusiastic about discussing, helping each other complete tasks, and are confident in expressing opinions; (3) Teachers are more enthusiastic and motivated with a more lively and conducive classroom setting for learning.